THE IMPLEMENTATION OF TRANSLANGUAGING IN TEACHING ENGLISH ON EFL SECONDARY LEVEL - Serin Winda Kisetya Fatma, - (2023)
The developments in the understanding of bilingualism have amplified the awareness of academics around the teaching methods in bilingual education. This study aimed to investigate the perceptions and practices of EFL high school in-service teachers towards translanguaging. This study would use a qualitative method for analyzing the data. From a qualitative method, the researcher aimed to implement a case study approach in conducting the recent study since there are some connections between the aim of the researcher and the concept of the case study. For observation, it was found out that there were 9 different actions in which language was used by an in-service teacher and each action could be categorized as translanguaging practices. Also, it was known that there were 9 actions that were categorized as themes of the major translanguaging functions, specifically the interpretive function; the managerial function; the managerial and interactive function; and the managerial and interpretive function. In addition to that, for an interview, there was only an action that was categorized as the theme of core characteristics of pedagogical translanguaging, specifically organization. Translanguaging fosters a good and dynamic learning environment in which students' L1 can be used to grasp course content better and foster a positive learning environment. Furthermore, the study could be a starting point for further investigations into translanguaging in English, where the L2 is rarely spoken outside of the classroom.